2019
DOI: 10.21467/ias.8.1.114-119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tithonia Diversifolia on Maize (Zea mays L.) Yield, Fertility and Infiltration Status of Two Clay Varied Soils

Abstract: Towards a more sustainable soil management through recycling of readily available weeds in Akure, Nigeria, different rates of Tithonia diversifolia (tithonia) were compared on a field trial to evaluate its effect on soil properties. The experiment was sited at two locations in South gate of the Federal University of Technology, Akure. Prior to the field establishment, a composite soil sample was collected and analyzed for physico-chemical properties. The sites were cleared and tilled. The experiment was laid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The result from the table showed that all treatments increased the exchangeable bases. This result correlates with the findings of Adeleye et al (2010), Ayeni and Ezeh (2017), Kobierski et al (2017), Dayo-Olagbende et al (2020), and Adekiya et al (2020) who stated that the application of amendments increases the exchangeable bases in the soil. The application of amendments significantly reduced the exchangeable acidity of the soil.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The result from the table showed that all treatments increased the exchangeable bases. This result correlates with the findings of Adeleye et al (2010), Ayeni and Ezeh (2017), Kobierski et al (2017), Dayo-Olagbende et al (2020), and Adekiya et al (2020) who stated that the application of amendments increases the exchangeable bases in the soil. The application of amendments significantly reduced the exchangeable acidity of the soil.…”
Section: Discussionsupporting
confidence: 91%
“…Green manure has a lot of benefits for the soil, which range from soil organic carbon enhancement, soil health improvement, high agronomic productivity (Hafifah et al, 2016), soil microbial biomass enhancement, and activity enhancement (Larkin, 2013). Tithonia diversifolia from the Asteraceae family, used as green manure due to its high nutritional composition, has proven effective in improving soil fertility (Hafifah et al, 2016), the physical properties of soil (Dayo-Olagbende et al, 2020; Hafifah et al, 2016), and crop yield (Babajide et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The biomass of Tithonia diversifolia has great nutrient content and is capable of extracting a high amount of nutrients from the soil ( Olabode et al, 2007 ). Its biomass is an effective source of nutrients and has been widely used in annual crops such as rice, maize ( Dayo-Olagbende et al, 2020 ; Kang et al, 2020 ). Its adaptability to a wide range of agro-ecological conditions, fast growth rate, and very high vegetative turnover make it suitable as a soil organic input ( Kiptot, 2008 ; Partey et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tithonia (Tithonia diversifolia) have a fast growth cycle, high nitrogen fixation capacity and P content (Scrase et al, 2019). T. diversifolia is used as green manure because this plant contains macro and micronutrients that can improve soil fertility (Dayo-Olagbende et al, 2019). T. diversifolia can increase growth and yields of sweet corn (Hidayat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%